Partial programs in access to the social values: technology that changes preschool education. - Molchaniuk, Olga; Babakina, Oksana; Dmytrenko, Kateryna; Kharkivska, Aryna; Kapustina, Olena (My University, 2020)
The article describes the current state and current issues of education in Ukraine. The relationship between the tasks of reforming general secondary education and the goal of preschool education in the context of continuity between the links of preschool and primary education has been established.The elaboration of the problem of education and the value orientations by both foreign and domestic researchers is analyzed. The importance of education of social values is revealed.The peculiarities of partial programs, their difference from complex ones are clarified. Partial programs for the education of social values in preschool institutions are described: «Aflatot», «The boundless world of playing with LEGO», «Learning to live together» and programs for the formation of computer literacy in preschool children («Computer literacy for children», «Media World for Preschoolers», «Fairy Tales and Paints»).The requirements for the education of social values of preschool children have been updated and the ways to implement the above programs have been presented. Each program identifies the purpose, key elements, principles and results of implementation. The connection between the principles of personality-oriented learning and the tasks of partial programs «Aflatot», «Boundless world of playing with LEGO», «Learning to live together», «Computer literacy for kids», «Media education for preschoolers», «Fairy tales and paints» is revealed. The article presents the practical aspect of using the programs: forms of work, topics of classes, description of materials and clarity for classes, etc.
Partial programs in access to the social values: technology that changes preschool education / O. Molchaniuk, O. Babakina, K. Dmytrenko, A. Kharkivska, O. Kapustina // Journal of critical reviews, 2020. – Vol 7. – Issue 14. – P. 2461–2470.
Keywords: social values, education of social values, partial programs, preschool institutions